(untitled) (Journal of Hama University, 2019)
This study aimed to compare between super elastic and heat-activated nickel-titanium orthodontic wires according to : (1) Yield strength ,(2) Elastic modulus following exposure to fluoride rinses. 40 distal cuts (20 mm) of NiTi Force I(Super elastic) and 40 distal cuts (20 mm) of Therma-TiLite (heat –activated) nickel-titanium orthodontic wires (0.017 in x0.025 in)( American Orthodontics Sheboygan, WI, USA) . were divided into equal groups (1) was passively exposed to oral environment of 20 volunteers for 1 month (2) with fluoride rinses . wires were tested, using tensile testing in a universal testing machine. Results: Fluoride treatment produced a statistically significant reduction in E, YS, and TS of the Ni-Ti wire (P ,< .05) was found after exposure to fluoride, upon comparison with oral cavity control treatment. Conclusions: These results suggest that using a fluoride rinses with nickel-titanium wire could decrease the mechanical properties and might damage the surface of the wire. . potentially contributing to prolonged orthodontic treatment.